Paradigma Kognitif “Client Centered” dalam Pendidikan Islam - Dwi Ulfa Nurdahlia (MA'ALIM: Jurnal Pendidikan Islam, 2022)
Abstract The cognitive paradigm of "client centered" is one of the paradigms that humanize humans, there are positive things in this paradigm that can adopting in the world of teaching. Because in the cognitive paradigm of "client centered" Rogers said that there is motivation in healthy people, namely self-actualization. This article will take the positive side of the "client centered" cognitive paradigm for the recognition of individual abilities that can developing in Islamic education that does not violate the rules in Islamic education. This study uses a qualitative approach using library research methods related to literature, either in the form of books or sources of notes and the results of previous research. Based on the results of the study on the "client centered" cognitive paradigm, it was found that; Every human being has a basic need for warmth, appreciation, acceptance, admiration, and love from others. This need is called the need for positive regard, which is further divided into 2, namely conditional positive regard (conditional) and unconditional positive regard (unconditional). There are five characteristics of a fully functioning person (openness to experience, existential life, belief in one's own organism, feeling of freedom, creativity). The client centered cognitive paradigm has positive meaning, which can make it easier for people to understand someone in education field, and can use Islamic glasses for research, and ultimately open up thinking insights. Abstrak Paradigma kognitif “client centered” merupakan salah satu paradigma yang memanusiakan manusia terdapat hal yang positif dalam paradigma ini yang dapat diadopsi dalam dunia pengajaran. Sebab dalam paradigma kognitif “client centered” Rogers menyampaikan bahwa terdapat motivasi pada orang yang sehat yaitu aktualisasi diri. Artikel kali ini akan megambil sisi positif dari paradigma kognitif “client centered” tentang pengakuan terhadap kemampuan diri individu yang dapat dikembangkan dalam pendidikan islam yang tidak menyalahi aturan dalam pendidikan islam. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode library research yang berkaitan dengan kepustakaan, baik berupa buku atau sumber catatan dan hasil penelitian terdahulu. Berdasar hasil kajian tentang paradigma kognitif “client centered” ditemukan bahwa; Setiap manusia memiliki kebutuhan dasar akan kehangatan, penghargaan, penerimaan, pengagungan, dan cinta dari orang lain. Kebutuhan ini disebut need for positive regard, yang terbagi lagi menjadi 2 yaitu conditional positive regard (bersyarat) dan unconditional positive regard (tak bersyarat). Terdapat lima sifat khas seseorang yang berfungsi sepenuhnya (keterbukaan pada pengalaman, kehidupan eksistensial, kepercayaan terhadap organisme sendiri, perasaan bebas, kreativitas). Paradigma kognitif client centered terdapat hal yang positif yang memberikan kemudahan untuk memahami seseorang dalam dunia pendidikan dan dapat dikaji dengan kacamata islam yang pada akhirnya membuka wawasan dalam berpikir.